Development of START-EDI guidelines for reporting equality, diversity and inclusion in research: a study protocol - Michael G Fadel; Rebecca Barnes; Amanda J Cross; Sally Hopewell; George B Hanna; Linda D Sharples; Peter Buckle; Brian D Nicholson; Patrick MM Bossuyt; Julie Hepburn; Vivian Welch; Jérémie F Cohen; et al. (BMJ Open, 2025)
Introduction Acknowledging equality, diversity and inclusion (EDI) in research is not only a moral imperative but also an important step in avoiding bias and ensuring generalisability of results. This protocol describes the development of STAndards for ReporTing EDI (START-EDI) in research, which will provide a set of minimum standards to help researchers improve their consistency, completeness and transparency in EDI reporting. We anticipate that these guidelines will benefit authors, reviewers, editors, funding organisations, healthcare providers, patients and the public.Methods and analysis To create START-EDI reporting guidelines, the following five stages are proposed: (i) establish a diverse, multidisciplinary Steering Committee that will lead and coordinate guideline development; (ii) a systematic review to identify the essential principles and methodological approaches for EDI to generate preliminary checklist items; (iii) conduct an international Delphi process to reach a consensus on the checklist items; (iv) finalise the reporting guidelines and create a separate explanation and elaboration document; and (v) broad dissemination and implementation of START-EDI guidelines. We will work with patient and public involvement representatives and under-served groups in research throughout the project stages.Ethics and dissemination The study has received ethical approval from the Imperial College London Research Ethics Committee (study ID: 7592283). The reporting guidelines will be published in open access peer-reviewed publications and presented in international conferences, and disseminated through community networks and forums.Trial registration number The project is pre-registered within the Open Science Framework (https://osf.io/8udbq/) and the Enhancing the Quality and Transparency of Health Research Network.